The Streptococcus mutans ability to survive in biofilms and during dental caries formation: scoping review - Anisauma UTAMANİNGYAS; Hening Tjaturina PRAMESTİ; Felisha Febriane BALAFİF (Dentistry Faculty, 2022)
Caries are the deterioration of dental hard tissue caused by acidic byproducts of bacterialcarbohydrate fermentation. The formation begins within the bacterial biofilm that covers the tooth's surface. Streptococcus mutans is the dominant bacteria in the biofilm, forming a multispecies biofilm on the tooth surface, growing, and surviving within it. S. mutans colony formation and acid formation can lead to tooth demineralization. The purpose of this scoping review is to determine the ability of S. mutans to survive in biofilms and during the formation of dental caries using articles from the chosen database. Articles published from 2016 until 2021 were searched for using the keywords: